SUMBER HUKUM SEBAGAI PILAR CIVIL LAW,COMMON LAW,DAN HUKUM ADAT - Juan delgibed sinlae; Fadil Masud; Helmi debora tobe; Intan marlencia lada (STKIP Subang, 2025)
Sources of law constitute fundamental pillars in the formation and implementation of legal systems, providing legitimacy, legal certainty, and normative direction for state governance. In the global legal context, three major legal traditions are widely recognized, namely civil law, common law, and customary law, each characterized by distinct sources of law. The problem addressed in this study lies in the limited comprehensive understanding of the position and role of legal sources within these traditions, particularly in the context of Indonesia’s pluralistic national legal system, which faces the challenges of globalization and digitalization. This study aims to analyze sources of law as the main pillars of the civil law, common law, and customary law traditions and to examine their relevance to the development of Indonesia’s national legal system. The research employs a normative legal research approach with a library research design. Data were collected through the examination of primary, secondary, and tertiary legal materials, which were analyzed qualitatively using a descriptive-analytical method and a comparative legal approach. The findings indicate that sources of law in the civil law tradition primarily emphasize statutory regulations as the main source of law, ensuring legal certainty and systematic order. In contrast, the common law tradition places judicial precedents or case law as a dominant source of law, allowing legal norms to evolve dynamically in response to social changes. Meanwhile, customary law functions as a living source of law that reflects local values and community-based wisdom. In the Indonesian context, these three legal traditions interact and complement one another, forming a pluralistic, adaptive, and justice-oriented national legal system. Strengthening legal literacy, internalizing Pancasila values, and integrating local wisdom through civic education are essential strategies to enhance public understanding and effective application of legal sources in the global and digital era.